2021
DOI: 10.1177/13674935211003774
|View full text |Cite
|
Sign up to set email alerts
|

DigiKnowIt News: Educating youth about pediatric clinical trials using an interactive, multimedia educational website

Abstract: Pediatric clinical trials allow for the testing of appropriate and effective treatments for children. However, some challenges exist with recruitment. This study examined the effectiveness of DigiKnowIt News, an interactive, multimedia website (which includes activities, videos, and comic books) designed to educate children about clinical trials. A randomized controlled trial was conducted in 2018 with 91 participants ( M age = 10.92 years; SD = 2.06). Participants were randomly assigned to intervention or wai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…Eight trials combined their online recruitment with offline advertising of the trial [28-29, 33-34, 38-39, 42, 45]. Offline recruitment included advertisements in communities, through healthcare professionals, and schools.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Eight trials combined their online recruitment with offline advertising of the trial [28-29, 33-34, 38-39, 42, 45]. Offline recruitment included advertisements in communities, through healthcare professionals, and schools.…”
Section: Resultsmentioning
confidence: 99%
“…All included trials reported acquiring consent from participants. Parental/caregiver consent was required in twelve of the trials [29-30, 34-35, 37-40, 42-45], waived in five of them [31, 33, 41, 46-47] and not reported in four [27-28, 32, 36]. Ten trials validated participants’ consent via attention-check questions, quality-check questions, ongoing consent, and orientation videos [29-31, 34, 37, 39, 41-42, 45, 47].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations